Innovation in vector control of dengue hemorrhagic fever using portable devices mechanical electric methods - Alvira Pascawati, Nur; Baskoro Tunggul Satoto, Tri; Mustiadi, Ikhwan; Lusiana Utari, Evrita (Intelektual Pustaka Media Utama, 2024)
This innovation was created to control the dengue hemorrhagic fever (DHF) vector population in the larval cycle because several previous control methods were considered less sensitive, effective, and efficient. To test the effectiveness of portable electrical-mechanical methods in controlling Aedes aegypti larvae. The research design was posttest only which was tested on 80-liter and 90-liter volume containers in light and dark colors. Statistical analysis used the independent samples t-test, and Pearson correlation (α=5%). Laboratory test results show that the average time needed to suck all the larvae in a light-colored container with a volume of 80 liters is 38 seconds (28-57 seconds) and a volume of 90 liters is 99.6 seconds (80-119 seconds). In a dark-colored container, the 80-liter volume is 50.8 seconds (3-89 seconds) and the 90-liter volume is 106.8 seconds (88-122 seconds). This tool sucks larvae faster in containers with a volume of 80 liters compared to a volume of 90 liters. The greater the volume of water and the higher the water surface, the longer it takes to suck the larvae. This tool is effective and efficient in speeding up the process of monitoring, collecting, and controlling larvae in large containers.